Photosynthetic Bradyrhizobium sp. Strain ORS285 Is Capable of Forming Nitrogen-Fixing Root Nodules on Soybeans (Glycine max) - Giraud, Eric (American Society for Microbiology, 2013)
The ability of photosynthetic Bradyrhizobium strains ORS285 and ORS278 to nodulate soybeans was investigated. While the nod gene-deficient ORS278 strain induced bumps only on soybean roots, the nod gene-containing ORS285 strain formed nitrogen-fixing nodules. However, symbiotic efficiencies differed drastically depending on both the soybean genotype used and the culture conditions tested.